1982
DOI: 10.1246/bcsj.55.3193
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Process of Titanium Tetrachloride with Ammonia in the Vapor Phase and Properties of the Titanium Nitride Formed

Abstract: The reaction products of gaseous TiCl4 with ammonia were TiCl4·5NH3 at 200 °C, TiCl4·5NH3, TiClN, and NH4Cl at 250–400 °C, TiCl4·5NH3, TiClN, TiNx, and NH4Cl at 450–650 °C, TiNx and NH4Cl at 700–1000 °C, and TiNx, NH4Cl, and HCl at 1100–1400 °C. The N/Ti atomic ratio, x, of the TiNx formed was 1.21 at 700 °C, 1.16 at 800 °C, 1.13 at 900 °C, and 1.10 above 1000 °C. The lattice constants of the TiNx formed are shown. The reaction process can be represented as follows: The reaction of gaseous TiCl4 with ammonia o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 3 publications
0
28
0
Order By: Relevance
“…In both cases the by-products ammonium halides, amide halides like M(NH 2 ) 3 X (M ¼ Ti, Zr; X ¼ Cl, Br) [14,17,18], different ammonia adducts such as MX 4 Á n NH 3 (M ¼ Ti, Zr; X ¼ Cl, Br, I; n ¼ 2, 4,5,6,8) [12,13,17,19,20] and (NH 4 ) 2 [MCl 6 ] (M ¼ Ti, Zr) [21,22] necessitate a purification step, which comprises sublimation or thermal treatment in an ammonia stream at the synthesis temperature (see Table 1). Especially the ammonia adducts and amides were observed as main products at low temperatures (<400 C) [20], while at higher temperatures (>750 C) binary nitrides with several compositions (Zr 3 N 4 , Zr 3 N, ZrN, MN x with M ¼ Ti, Zr) are obtained [19,20,22]. For higher crystallinity of the product the purified nitride halides were annealed at synthesis temperatures for the a-polymorph (180-400 C) and at higher temperatures for the b-phase (900-1000 C) [16].…”
Section: Abbreviationsmentioning
confidence: 99%
“…In both cases the by-products ammonium halides, amide halides like M(NH 2 ) 3 X (M ¼ Ti, Zr; X ¼ Cl, Br) [14,17,18], different ammonia adducts such as MX 4 Á n NH 3 (M ¼ Ti, Zr; X ¼ Cl, Br, I; n ¼ 2, 4,5,6,8) [12,13,17,19,20] and (NH 4 ) 2 [MCl 6 ] (M ¼ Ti, Zr) [21,22] necessitate a purification step, which comprises sublimation or thermal treatment in an ammonia stream at the synthesis temperature (see Table 1). Especially the ammonia adducts and amides were observed as main products at low temperatures (<400 C) [20], while at higher temperatures (>750 C) binary nitrides with several compositions (Zr 3 N 4 , Zr 3 N, ZrN, MN x with M ¼ Ti, Zr) are obtained [19,20,22]. For higher crystallinity of the product the purified nitride halides were annealed at synthesis temperatures for the a-polymorph (180-400 C) and at higher temperatures for the b-phase (900-1000 C) [16].…”
Section: Abbreviationsmentioning
confidence: 99%
“…Trimethylamine reduces Ti (IV) to Ti(III) and forms a complex with resulting titanium trichlorideTiCl 3 :2NH 3 . Saeki et al [9 ] observed TiCl 4 :5NH 3 as a product of the gas phase reaction between TiCl 4 and NH 3 at a temperature below 220°C, which presumably consists of a mixture of NH 4 Cl with an ammonia adduct of the partially aminolyzed TiCl 4 . In the temperature range between 220 o C and 430 o C TiCl 4 :5NH 3 decomposes to ClTiN, which at higher temperatures reacts with ammonia forming TiN x powder [9].…”
Section: Introductionmentioning
confidence: 99%
“…Saeki et al [9 ] observed TiCl 4 :5NH 3 as a product of the gas phase reaction between TiCl 4 and NH 3 at a temperature below 220°C, which presumably consists of a mixture of NH 4 Cl with an ammonia adduct of the partially aminolyzed TiCl 4 . In the temperature range between 220 o C and 430 o C TiCl 4 :5NH 3 decomposes to ClTiN, which at higher temperatures reacts with ammonia forming TiN x powder [9]. The thermochemistry of gas-phase species relevant to TiN CVD has been studied theoretically by Allendorf et al [10 ] who reported a 17 kcal mol -1 exothermic enthalpy of the 1:1 complex formation between TiCl 4 and NH 3 and a 20 kcal mol -1 endothermic decomposition energy of this complex toward Cl 3 TiNH 2 and HCl.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal cracking is only of importance at temperatures above 1000 C. [10,11] In all cases, post-treatment is necessary to remove the by-product NH 4 Cl, as well as to destroy formed chlorine-containing intermediates. Post-treatment at 900 C in an ammonia atmosphere leads to mainly chlorine-free powders with a particle size < 1 lm, and a spherical morphology.…”
Section: Introductionmentioning
confidence: 99%